Strategi Pengembangan Usaha Produk Olahan Ikan Lele (Clarias sp.) di Desa Hangtuah Kecamatan Perhentian Raja Kabupaten Kampar Provinsi Riau - Mega Intan Panjaitan; Darwis; Lamun Bathara (Jurusan Sosial Ekonomi Perikanan, 2021)
This research was conducted in June 2020 in Hangtuah village, Perhentian Raja Sub District, Kampar Regency, Riau Province.This study aims to calculate the income earned and to analyze the strategy in developing a business of processed catfish (Clarias sp) products in Hangtuah village. The method used is a survey method by conducting direct observations in the field by collecting data through interviews based on questionnaires, the population in this study are housewives who are members of the catfish processing business group in Hangtuah village, namely the Mina Sejahtera group, which amounts to 10 members. The results showed that the income per month of catfish processing business carried out by the Mina Sejahtera group was IDR 424,510. SWOT analysis resulted in 12 alternative strategies that can be used by catfish processing products. The results of the calculation of the score of each strategy can be ranked as seen from the number of interests generated. Rank 1 (one) to 3 (three) is a strategy that is prioritized for use in the development of marketing of processed catfish products. The three strategies are: (WO1) Promoting processed catfish products with brochures / printed media and online social media so as to attract potential consumers; (SO1) Can develop new product innovations by paying more attention to the quality of processed catfish products so that they can be sold in the market; (ST1) Maintaining the quality and characteristics of processed catfish products.